Improving Teacher Job Satisfaction Through Organizational Commitment and Organizational Citizenship Behavior in The Digitalization Era - Ari Kartiko; Guntur Arie Wibowo; Lisda Van Gobel; Adi Wijayanto; Nanda Saputra (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
To increase the productivity and maximum efficiency of teachers at work, job satisfaction is an important concern for every organization. Increasing job satisfaction is important for organizations to increase commitment and organizational citizen behavior (OCB). The effect of organizational commitment and organizational citizenship behavior (OCB) on teacher job satisfaction is the subject of this research. This research was conducted using a quantitative approach with the help of IBM SPSS version 25, and the research instruments were tested for validity and reliability. 71 respondents were taken as a sample through the census method, and data was collected through a questionnaire. The results showed that the organizational commitment variable (X1) influenced teacher job satisfaction (Y1), as shown by testing the t-test hypothesis, where Tcount>Ttable (5.413>1.995) and a significant level that was less than 0.05, namely (0.021< 0.05). Organizational citizen behavior (OCB) variable (X2) influences job satisfaction (Y1).